Steel plate shear walls with partial length connection to vertical boundary element. (August 2021) - Haji Mirsadeghi, Mohammad Reza; Fanaie, Nader
Abstract: This research project aims to propose an innovative analytical method to evaluate steel plate shear wall with partial length connection to vertical boundary element which lacks the connection at the middle height of VBE. In this type of steel shear walls, reducing the length of the connection between infill and vertical boundary element results in a reduction in the flexure and stiffness demand on the vertical boundary elements. Push-over loading was carried out on four small-scale designed test specimens so as to investigate the quality of tension field formation in web plate by changing not connected length ratio. Then numerical model was employed to develop comprehensive study on web plate stress state due to the formation of tension field by changing not connected length ratio. Firstly, the formation of parallel tension strips in the infill plate of the steel shear wall with different partial length connections to vertical boundary elements in specified range of lack of connection was confirmed. Based on aforementioned experimental and numerical study evidence, governing equations have been developed for this analytical solution, including panel shear strength, tension field inclination angle and minimum stiffness requirements in vertical boundary elements.